Profitability and Capital Structure's Effect on Firm Value: The Moderating Influence of Company Size - Reisha Savira Mulyawati Ardiansyah; Eriana Kartadjumena (Syntax Idea)
This study aims to examine and test the influence of profitability and capital structure on firm value, with company size as a moderating variable in technology companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. This quantitative research employs convenience sampling with a sample size of 32 companies. The data used in this study is secondary data, comprising 94 financial statements. The analysis was conducted using moderated regression analysis with the assistance of eViews version 13. The results indicate that profitability does not affect firm value, whereas capital structure does influence firm value. Additionally, company size weakens the effect of profitability and capital structure on firm value